2015
DOI: 10.1124/mol.115.099978
|View full text |Cite
|
Sign up to set email alerts
|

AT-1001 Is a Partial Agonist with High Affinity and Selectivity at Human and Rat α3β4 Nicotinic Cholinergic Receptors

Abstract: AT-1001 [N-(2-bromophenyl)-9-methyl-9-azabicyclo[3.3.1] nonan-3-amine] is a high-affinity and highly selective ligand at a3b4 nicotinic cholinergic receptors (nAChRs) that was reported to decrease nicotine self-administration in rats. It was initially reported to be an antagonist at rat a3b4 nAChRs heterologously expressed in HEK293 cells. Here we compared AT-1001 actions at rat and human a3b4 and a4b2 nAChRs similarly expressed in HEK 293 cells. We found that, as originally reported, AT-1001 is highly selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…AT-1001 is a partial agonist that acts functionally as an antagonist by causing rapid desensitization (Cippitelli et al, 2015) (Figure 3B). This compound displays sub-nanomolar affinity to the human a3b4 receptor and is $200-fold selective for this subtype over a4b2 (Tuan et al, 2015). Our structure revealed that AT-1001 binds at the orthosteric sites (Figure 3B).…”
Section: Ligand Binding and Selectivitymentioning
confidence: 85%
“…AT-1001 is a partial agonist that acts functionally as an antagonist by causing rapid desensitization (Cippitelli et al, 2015) (Figure 3B). This compound displays sub-nanomolar affinity to the human a3b4 receptor and is $200-fold selective for this subtype over a4b2 (Tuan et al, 2015). Our structure revealed that AT-1001 binds at the orthosteric sites (Figure 3B).…”
Section: Ligand Binding and Selectivitymentioning
confidence: 85%
“…Competition binding experiments at hα3rβ4 and hα3hβ4 also demonstrated that these amino acids were responsible for a modest but significant (14-fold) difference in the affinity of binding of TMAQ to nAChRs containing the human and rat α4 subunit. Similarly, in 2015, Tuan et al reported AT-1001 (Figure 2) as a human selective α3β4 nAChR ligand with similar K i s at human and rat α4β2 nAChRs, while 20 times higher affinity at the human than rat α3β4 nAChRs [43].…”
Section: Resultsmentioning
confidence: 74%
“…High concentrations of the α4β2 antagonist DhβE that are needed to block their activation with 90 µM nicotine can also block α3β4 (Harvey, Maddox, & Luetje, ). Consequently, to distinguish the contributions of α4β2 and α3β4 nAChRs to network activity, we used sazatidine‐A (SAZ‐A), a partial agonist at rat α4β2 nAChRs (DeDominicis et al, ; Tuan et al, ) which potently desensitizes rat α4β2 but not rat α3β4 nAChRs (Xiao et al, ). We also used AT‐1001, a partial agonist at rat α3β4 nAChRs that is known to desensitize rat α3β4 and human α4β2 nAChRs (Tuan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of SAZ‐A and AT‐1001 were chosen based on the maximal desensitization each drug would cause at its target receptor (Tuan et al, ; Xiao et al, ), which coincides with the maximal activation of each receptor. As they are partial agonists, the long application time will desensitize the target nAChR receptor, essentially giving rise to a ‘time‐averaged antagonism’ (Hulihan‐Giblin et al, ).…”
Section: Resultsmentioning
confidence: 99%